Management defines species turnover of bees and flowering plants in vineyards. (16th December 2013) - Kehinde, Temitope; Samways, Michael J.
Abstract Effects of land use and management on plant and pollinator diversity at the local scale have been reported. However, there is little information available on the spatial and temporal aspects of plant‐pollinator mutualist diversity relative to farm management. Information on these aspects will provide a better understanding of agri‐environment schemes in a conservation context. In the present study, we use additive partitioning (sum of within and among community diversity) to determine local (alpha) diversity and spatial and temporal (beta) diversity of bees and flowering plants in differently managed vineyards and adjacent natural vegetation in the Cape Floristic Region biodiversity hotspot. Alpha, spatial beta and temporal beta diversities accounted for 18–61%, 19–72% and 7–36% of total bee diversity, respectively. Local diversity and spatial turnover of flowering plant diversity were significantly higher in the natural vegetation compared with organic and conventional vineyards. Spatial turnover of bees varied significantly with longitudinal coordinates of study sites. We show that wildlife‐friendly management practices ensure species‐rich plant communities that promote pollinator diversity. We demonstrate the necessity to conserve mosaics of natural and semi‐natural habitats in agricultural landscapes to conserve plant and bees. Our findings demonstrate the need to include spatial factors of habitats for effective conservation in this region.